How to ask the best probing questions - Fadem, T. J. (Terry Jay), 1948- (FT Press Delivers elements., 2010)
"This Element is an excerpt from The art of asking: ask better questions, get better answers (ISBN: 9780137144242) by Terry J. Fadem. Ask the probing questions that get you past deceit, defensiveness, half-truths, secrecy, and misdirection"--Resource description page.